Trendsetter Muballigh di Medsos: Analisis Framing Instagram Felix Siauw dan Hanan Attaki - Latifah, Nor; Romario, Romario (IAIN Palangka Raya, 2019)
The increasing use of Instagram is dominated by users around the age of 15-30 years. The majority who followed in Instagram were famous public figures such as celebrities, political figures and religious leaders. With this Instagram, da'i or preachers can convey their messages easily and free through photos and captions or short videos. This study is important to see how Instagram as a new media is able to become a trendsetter for wellknown Ustadz like Felix Siauw and Hanan Attaki. This study uses a qualitative research method using the framing model as proposed by Robert N. Entman by observing how a discourse or communication is displayed in the public space. The finding confirmed that the framing model of Felix Siauw and Hanan Attaki has similarities in preaching Islam through Instagram social media using short posts or short videos and interesting captions. However, both of them have different tendencies, in which Felix Siauw is more dominant in discussing social and political issues while Hanan Attaki is more dominant in discussing good advice or about love between men and women.